RF and Microwave Microelectronics Packaging II - Kuang, Ken.; Sturdivant, Rick.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
Reviews RF, microwave, and microelectronics assembly process, quality control, and failure analysis Bridges the gap between low cost commercial and hi-res RF/Microwave packaging technologies Engages in an in-depth discussion of challenges in packaging and assembly of advanced high-power amplifiers This book presents the latest developments in packaging for high-frequency electronics. It is a companion volume to "RF and Microwave Microelectronics Packaging" (2010) and covers the latest developments in thermal management, electrical/RF/thermal-mechanical designs and simulations, packaging and processing methods, and other RF and microwave packaging topics. Chapters provide detailed coverage of phased arrays, T/R modules, 3D transitions, high thermal conductivity materials, carbon nanotubes and graphene advanced materials, and chip size packaging for RF MEMS. It appeals to practicing engineers in the electronic packaging and high-frequency electronics domain, and to academic researchers interested in understanding the leading issues in the commercial sector. It is also a good reference and self-studying guide for students seeking future employment in consumer electronics.
Chapter1. Introduction to RF and Microwave Microelectronic Packaging -- Chapter2. Packaging of Transmit/Receive Modules -- Chapter3. 3D Transitions and Connections -- Chapter4. Electromagnetic Shielding for RF & Microwave Packages -- Chapter5. Design of C-Band Interdigital Filter and Compact C-band Hairpin Bandpass Film Filter on Thin Film Substrate -- Chapter6. Research on High-reliable Low-loss HTCC Technology Applied in Millimeter Wave SMT Package -- Chapter7. Chip Size Packaging (CSP) for RF MEMS Devices -- Chapter8. The challenge in packaging and assembly the advanced power amplifiers -- Chapter9. High Thermal Conductivity Materials - Aluminum Diamond, Aluminum Silicon Carbide, and Copper Diamond -- Chapter10. Advancement in High Thermal Conductive Graphite for Microelectronic Packaging -- Chapter11. Carbon nanotubes and graphene for microwave/RF electronics packaging.
Keywords: Electronics; Telecommunication; Electronic circuits; Electronics and Microelectronics, Instrumentation; Microwaves, RF Engineering and Optical Communications; Electronic Circuits and Systems